Syntheses and Applications of Singh’s Catalyst - Khandelwal, Manisha; Ray, Sumit Kumar; Khangarot, Rama Kanwar (Synthesis, 2020)
Singh’s catalyst has emerged as one of the most promising and valuable catalysts in the field of asymmetric synthesis. Since its discovery, it has proven to be one of the best organocatalysts for asymmetric direct aldol reactions, and is equally efficient in aqueous and organic media. In this Short Review, we summarize reactions utilizing Singh’s catalyst under various conditions.1 Introduction2 Synthesis of Singh’s Catalyst3 Applications in Asymmetric Synthesis4 Conclusion
Keywords: Singh’s catalyst; asymmetric direct aldol reaction; organocatalysis; enantioselective; diastereoselective; chemoenzymatic synthesis